A tale of two independence movements: how do citizens encounter issues of international law and democratic theory? - Levintova, Ekaterina (Nationalities papers, 2017)
Foreign policy events, including secessionism and independence movements, become objectified for most citizens through media coverage. Accordingly, I look at the coverage of Kosovo's and Scotland's bids for independence in the two top national newspapers, The New York Times and The Washington Post. Scholarship in international law, democratic theory, and comparative politics might have valuable insights on independence processes, but it is the media frames inspired by these strands of theoretical literature that shape public opinion and/or reflect policy-makers’ preferences (and biases) in the foreign policy arena. I find that print media can engage in theoretically sophisticated coverage of secessionist movements, which often echoes scholarly insights derived from the relevant academic literature. The two European case studies show consistent application of tropes and frames that one would find in the academic publications on the subject. Yet these cases also illustrate profound differences in media framing not reducible to objective legal and political differences between the two events. US foreign policy considerations also appear to play a role in explaining variance in media frames.